Treatment Progress and Behavior Following 2 Years of Inpatient Sex Offender Treatment: A Pilot Investigation of Safe Offender Strategies. (February 2017) - Stinson, Jill D.; Becker, Judith V.; McVay, Lee Ann
Emerging research highlights the role of self-regulation in the treatment of sexual offenders. Safe Offender Strategies (SOS) is a manualized sex offender treatment program that emphasizes the role of self-regulation and self-regulatory skills development in sex offender treatment, particularly for offenders with serious mental illness and intellectual/developmental disabilities. The current study involves 156 adult male sexual offenders in an inpatient psychiatric setting who received SOS treatment for a period ranging from 6 months to 1 year. Participants' baseline and treatment data were obtained from archival medical records describing 1 year pre-treatment and up to 2 years of treatment participation. Dependent variables included monthly count rates of verbal and physical aggression and contact and noncontact sexual offending, as well as sexual deviancy attitudes, self-regulatory ability, and cooperation with treatment and supervision, as measured by the Sex Offender Treatment Intervention and Progress Scale (SOTIPS). Data were examined via paired-samples t tests, regression, and multilevel modeling, examining the impact of overall percentage of SOS groups attended over time, comparing participants' baseline measures to data from 2 years of treatment. The impact of predicted risk was also evaluated. Significant treatment dose effects were identified for improvements in aggression, sexual offending, and indicators of treatment compliance and change. These findings suggest that the skills-based, self-regulation approach utilized in SOS may be effective in improving clients' aggressive and sexual behaviors, attitudes toward their offenses and treatment, and self-regulatory ability over time. Implications for further research and treatment generalizability are discussed.